Autophagy Mediates Interleukin-1β Secretion in Human Neutrophils - Leonardo Iula; Irene A. Keitelman; Florencia Sabbione; Federico Fuentes; Mauricio Guzman; Jeremías Gastón Galletti; Pehuén Pereyra Gerber; Matías Ostrowski; Jorge R. Geffner; Jorge R. Geffner; Carolina C. Jancic; Carolina C. Jancic; et al. (Frontiers in Immunology, 2018)
Interleukin-1β (IL-1β), a major pro-inflammatory cytokine, is a leaderless cytosolic protein whose secretion does not follow the classical endoplasmic reticulum-to-Golgi pathway, and for which a canonical mechanism of secretion remains to be established. Neutrophils are essential players against bacterial and fungi infections. These cells are rapidly and massively recruited from the circulation into infected tissues and, beyond of displaying an impressive arsenal of toxic weapons effective to kill pathogens, are also an important source of IL-1β in infectious conditions. Here, we analyzed if an unconventional secretory autophagy mechanism is involved in the exportation of IL-1β by these cells. Our findings indicated that inhibition of autophagy with 3-methyladenine and Wortmannin markedly reduced IL-1β secretion induced by LPS + ATP, as did the disruption of the autophagic flux with Bafilomycin A1 and E64d. These compounds did not noticeable affect neutrophil viability ruling out that the effects on IL-1β secretion were due to cell death. Furthermore, VPS34IN-1, a specific autophagy inhibitor, was still able to reduce IL-1β secretion when added after it was synthesized. Moreover, siRNA-mediated knockdown of ATG5 markedly reduced IL-1β secretion in neutrophil-differentiated PLB985 cells. Upon LPS + ATP stimulation, IL-1β was incorporated to an autophagic compartment, as was revealed by its colocalization with LC3B by confocal microscopy. Overlapping of IL-1β-LC3B in a vesicular compartment peaked before IL-1β increased in culture supernatants. On the other hand, stimulation of autophagy by cell starvation augmented the colocalization of IL-1β and LC3B and then promoted neutrophil IL-1β secretion. In addition, specific ELISAs indicated that although both IL-1β and pro-IL-1β are released to culture supernatants upon neutrophil stimulation, autophagy only promotes IL-1β secretion. Furthermore, the serine proteases inhibitor AEBSF reduced IL-1β secretion. Moreover, IL-1β could be also found colocalizing with elastase, suggesting both some vesicles containing IL-1β intersect azurophil granules content and that serine proteases also regulate IL-1β secretion. Altogether, our findings indicate that an unconventional autophagy-mediated secretory pathway mediates IL-1β secretion in human neutrophils.